Cardiomyocyte OTUD1 drives diabetic cardiomyopathy via directly deubiquitinating AMPKα2 and inducing mitochondrial dysfunction - Xue Han; Ruyi Zheng; Jiajia Zhang; Yanan Liu; Ze Li; Guoxuan Liu; Jianing Zheng; Weiqi Li; Zijun Liang; Mengyang Wang; Jie Yu; Qiaojuan Shi; et al. (Nature Communications)
Abstract Deubiquitinating modification of proteins is involved in the pathogenesis of diseases. Here, we investigated the role and regulating mechanism of a deubiquitinating enzyme (DUB), ovarian tumor domain-containing protein 1 (OTUD1), in diabetic cardiomyopathy (DCM). We find a significantly increased OTUD1 expression in diabetic mouse hearts, and single-cell RNA sequencing shows OTUD1 mainly distributing in cardiomyocytes. Cardiomyocyte-specific OTUD1 knockout prevents cardiac hypertrophy and dysfunction in both type 2 and type 1 diabetic male mice. OTUD1 deficiency restores cardiac AMPK activity and mitochondrial function in diabetic hearts and cardiomyocytes. Mechanistically, OTUD1 binds to AMPKα2 subunit, deubiquitinates AMPKα2 at K60/K379 sites, and then inhibits AMPKT172 phosphorylation through impeding the interaction of AMPKα2 and its upstream kinase CAMKK2. Finally, silencing AMPKα2 in cardiomyocytes abolishes the cardioprotective effects of OTUD1 deficiency in diabetic mice. In conclusion, this work identifies a direct regulatory DUB of AMPK and presents a OTUD1-AMPK axis in cardiomyocytes for driving DCM.